Transgression of Corporate Governance in South Africa’s State-Owned Enterprises - Raseala, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
State-owned enterprises (SOEs) play a very important role in South Africa’s socio-economic development trajectory, and a strong, transparent and accountable government is central to such course. Accordingly, the immediate attention for the post-apartheid government was to lay the basic foundation for democracy and good governance. SOEs are critical mechanisms to assist government to achieve economic growth, service delivery, poverty reduction, employment creation and in the development of the country’s strategic sectors such as finance, energy, transport, telecommunications, manufacturing and natural resources. However, most of these important SOEs in South Africa are characterised by poor leadership, maladministration, corruption, antagonism, animosity, impunity, weak financial reporting, chronic under-performance, debt burdens, insufficient performance monitoring and accountability systems. Some of these setbacks are associated with corporate governance failures including weak managerial accountability, excessive politicisation and unclear objectives. As a result, SOEs no longer contribute strongly to development or perform their public service role effectively and efficiently thereby undermining government’s intentions to achieve growth and development objectives. The paper therefore argues that the absence of effective good corporate governance is the one of the major reasons of failures of most SOEs to fulfil the mandate which they were created for. Basis of the paper is that, the success of SOEs is dependent on whether the governance systems are placed towards responsiveness to the needs of individuals, communities and society in general. This paper therefore strives to explore the corporate governance quagmires in the SOE sector which impede socio-economic development efforts of government. The paper concludes that SOEs are muddled with governance problems which are the nemeses of good corporate governance, therefore, governance transformation in the SOE sector in is essential.
Journal article published in the International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Accountability; Corporate Governance; Good Governance; State-Owned Enterprises; Transgression (Ethics)